Structural, electronic, magnetic and mechanical properties of Mn-based antiperovskites - Benmiloud, Reguia; Laggoun, Ibrahim (Laghouat : Université Amar Telidji - Département des sciences de la matière, 2021)
The purpose of this work is the determination of the structural, electronic, magnetic, and mechanical properties of Mn-basedantiperovskites Mn3AX (A = Zn, Ga), (X=C, N). The calculations were performed in the framework of the density functional theory (DFT), within the two methods : pseudo potentials (PP) and the Full Potential Linear Augmented Planes Waves (FP-LAPW). The generalized gradient approximation proposed by Wu-Cohen (GGA-WC) is used for modeling exchange-correlation effects. The electronic structures and magnetic properties of Mn-based antiperovskites were studied using the GGA, GGA + U and spin orbit coupling methods. The inclusion of Hubbard U potential gives significant effects on the electronic density of states, the structure of the energy band and the magnetic moment. The results obtained were commented and compared with the available experimental data. A very good agreement was found between the calculated results and those obtained from the experimental. The mechanical properties of these compounds have been investigated also, and we have found that these compounds are stable mechanically and showed anisotropic character.